Family practice research in the African region 2020-2022 - Robert J. Mash; Klaus Von Pressentin (AOSIS, 2024)
Background: The African region produces a small proportion of all health research, including primary health care research. The SCOPUS database only lists the African Journal of Primary Health Care Family Medicine (PHCFM) and the South African Family Practice Journal (SAFP) in the field of family practice. Aim: To review the nature of all original research (2020-2022) published in PHCFM and SAFP. Setting: African region. Method: All 327 articles were included. Data were extracted into REDCap, using a standardised tool and exported to the Statistical Package for Social Sciences. Results: The median number of authors was 3 (interquartile range [IQR]: 2-4) and institutions and disciplines 1 (IQR: 1-2). Most authors were from South Africa (79.8%) and family medicine (45.3%) or public health (34.2%). Research focused on integrated health services (76.1%) and was mostly clinical (66.1%) or service delivery (37.9%). Clinical research addressed infectious diseases (23.4%), non-communicable diseases (24.6%) and maternal and women's health (19.4%). Service delivery research addressed the core functions of primary care (35.8%), particularly person-centredness and comprehensiveness. Research targeted adults and older adults (77.0%) as well as health promotion or disease prevention (38.5%) and treatment (30.9%). Almost all research was descriptive (73.7%), mostly surveys. Conclusion: Future research should include community empowerment and multisectoral action. Within integrated health services, some areas need more attention, for example, children, palliative and rehabilitative care, continuity and coordination. Capacity building and support should enable larger, less-descriptive and more collaborative interdisciplinary studies with authors outside of South Africa. Contribution: The results highlight the strengths and weaknesses of family practice research in Africa.